2020
DOI: 10.3389/fnins.2020.592954
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Assessment of Tone Production of Prelingually-Deafened Mandarin-Speaking Children With Cochlear Implants

Abstract: Objective The purpose of the present study was to investigate Mandarin tone production performance of prelingually deafened children with cochlear implants (CIs) using modified acoustic analyses and to evaluate the relationship between demographic factors of those CI children and their tone production ability. Methods Two hundred seventy-eight prelingually deafened children with CIs and 173 age-matched normal-hearing (NH) children participated in the study. Thirty-six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…However, due to the incomplete auditory input delivered through the device, possible neural degeneration associated with auditory deprivation, and potentially altered cognitive processes [see Başkent et al (2016) for a review], prelinguallydeafened children with CIs still show deficits in many speech, language, and hearing skills especially for pitch-related tasks in comparison to their peers with normal hearing (NH) (Chin et al 2003;Geers, 2004;Zeng, 2004;Hopyan-Misakyan et al 2009;Nittrouer 2009;Ren et al 2018;Chatterjee et al 2019;Damm et al 2019). Numerous studies have reported that prelinguallydeafened children with CIs demonstrated significantly poorer performance than peers with NH in perception and/or production of lexical tones and sentence intonation (e.g., Lee et al 2002;Peng et al 2004Peng et al , 2008Han et al 2007Han et al , 2009Zhou et al 2013;Mao & Xu 2017;Holt et al 2018;Deroche et al 2019;Mao et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the incomplete auditory input delivered through the device, possible neural degeneration associated with auditory deprivation, and potentially altered cognitive processes [see Başkent et al (2016) for a review], prelinguallydeafened children with CIs still show deficits in many speech, language, and hearing skills especially for pitch-related tasks in comparison to their peers with normal hearing (NH) (Chin et al 2003;Geers, 2004;Zeng, 2004;Hopyan-Misakyan et al 2009;Nittrouer 2009;Ren et al 2018;Chatterjee et al 2019;Damm et al 2019). Numerous studies have reported that prelinguallydeafened children with CIs demonstrated significantly poorer performance than peers with NH in perception and/or production of lexical tones and sentence intonation (e.g., Lee et al 2002;Peng et al 2004Peng et al , 2008Han et al 2007Han et al , 2009Zhou et al 2013;Mao & Xu 2017;Holt et al 2018;Deroche et al 2019;Mao et al 2020).…”
Section: Introductionmentioning
confidence: 99%